Genomic insights into ecological adaptation of oaks revealed by phylogenomic analysis of multiple species - Tian-Rui Wang; Xin Ning; Si-Si Zheng; Yu Li; Zi-Jia Lu; Hong-Hu Meng; Bin-Jie Ge; Gregor Kozlowski; Meng-Xiao Yan; Yi-Gang Song (Plant Diversity)
Understanding the ecological adaptation of tree species can not only reveal the evolutionary potential but also benefit biodiversity conservation under global climate change. Quercus is a keystone genus in Northern Hemisphere forests, and its wide distribution in diverse ecosystems and long evolutionary history make it an ideal model for studying the genomic basis of ecological adaptations. Here we used a newly sequenced genome of Quercus gilva, an evergreen oak species from East Asia, with 18 published Fagales genomes to determine how Fagaceae genomes have evolved, identify genomic footprints of ecological adaptability in oaks in general, as well as between evergreen and deciduous oaks. We found that oak species exhibited a higher degree of genomic conservation and stability, as indicated by the absence of large-scale chromosomal structural variations or additional whole-genome duplication events. In addition, we identified expansion and tandem repetitions within gene families that contribute to plant physical and chemical defense (e.g., cuticle biosynthesis and oxidosqualene cyclase genes), which may represent the foundation for the ecological adaptation of oak species. Circadian rhythm and hormone-related genes may regulate the habits of evergreen and deciduous oaks. This study provides a comprehensive perspective on the ecological adaptations of tree species based on phylogenetic, genome evolutionary, and functional genomic analyses.